2020
DOI: 10.3390/pathogens9070570
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analyses of Rotavirus A from Cattle in Uruguay Reveal the Circulation of Common and Uncommon Genotypes and Suggest Interspecies Transmission

Abstract: Uruguay is one of the main exporters of beef and dairy products, and cattle production is one of the main economic sectors in this country. Rotavirus A (RVA) is the main pathogen associated with neonatal calf diarrhea (NCD), a syndrome that leads to significant economic losses to the livestock industry. The aims of this study are to determine the frequency of RVA infections, and to analyze the genetic diversity of RVA strains in calves in Uruguay. A total of 833 samples from dairy and beef calves were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
62
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(66 citation statements)
references
References 53 publications
3
62
1
Order By: Relevance
“…This is remarkable given the high frequency of detection of these agents at the farm level. The detection frequencies of rotavirus in diarrheic (24.2%) or non-diarrheic (11.1%) calves in our study were much lower than those reported by RT-qPCR by Castells et al [46] in the same country using mostly the same sample set (72.1% and 59.9%, respectively). In our study, this frequency is probably underestimated considering that the detection limit and the sensitivity of the antigen-capture ELISA are lower than RT-qPCR, mainly in subclinical infections, and neutralizing antibodies derived either from colostrum or active immune responses may interfere with viral detection by antigen-capture ELISA [47].…”
Section: Discussioncontrasting
confidence: 87%
“…This is remarkable given the high frequency of detection of these agents at the farm level. The detection frequencies of rotavirus in diarrheic (24.2%) or non-diarrheic (11.1%) calves in our study were much lower than those reported by RT-qPCR by Castells et al [46] in the same country using mostly the same sample set (72.1% and 59.9%, respectively). In our study, this frequency is probably underestimated considering that the detection limit and the sensitivity of the antigen-capture ELISA are lower than RT-qPCR, mainly in subclinical infections, and neutralizing antibodies derived either from colostrum or active immune responses may interfere with viral detection by antigen-capture ELISA [47].…”
Section: Discussioncontrasting
confidence: 87%
“…The current strategy to control the disease in cattle is based on the vaccination of cows during the last third of gestation to protect calves by transferring passive maternal antibodies through the ingestion of colostrum [44]. Although vaccines seem not to be effective in preventing RVA infection, they significantly reduce morbidity, the severity of diarrhea, and mortality related to RVA [44,45].…”
Section: Rotavirusmentioning
confidence: 99%
“…The interspecies transmission has been documented for rotavirus [45], coronavirus [169], astrovirus [88,92], kobuvirus [131,170], pestivirus [171], and enterovirus [172,173]. Notably, the zoonotic potential has been discussed for rotavirus [45], coronavirus [174], nebovirus [175], and enterovirus [172,173].…”
Section: Interspecies Transmissionmentioning
confidence: 99%
“…Understanding the diversity of strains in various animal populations is important for animal health and farming practices, as well as being informative for the contextualisation of zoonotic transmission events. Castells et al reported detection of rotavirus in calves reared for beef and dairy production in Uruguay [ 24 ]. Multiple genotypes associated with bovine disease were detected including G6P[11] (40.4%), G6P[5] (38.6%), G10P[11] (19.3%), as well as the uncommon genotype G24P[33] (1.8%) [ 24 ].…”
mentioning
confidence: 99%
“…Castells et al reported detection of rotavirus in calves reared for beef and dairy production in Uruguay [ 24 ]. Multiple genotypes associated with bovine disease were detected including G6P[11] (40.4%), G6P[5] (38.6%), G10P[11] (19.3%), as well as the uncommon genotype G24P[33] (1.8%) [ 24 ].…”
mentioning
confidence: 99%